2018
DOI: 10.5539/jas.v10n9p468
|View full text |Cite
|
Sign up to set email alerts
|

Maize Sowing Speeds and Seed-Metering Mechanisms

Abstract: The intensifying use of machines in agriculture to increase operational capacity requires investments in more powerful and automated machines capable of working at higher speeds to meet the demands of agricultural activities. The objective of this study was to evaluate the sowing quality of a second crop maize using a pneumatic sowing machine equipped with two seed-metering devices at different displacement speeds. The statistical design was a randomized block design arranged in 6 × 2 factorial, with 4 replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…It was observed that the seed metering mechanism on the seed drill implements performed better in regulating the placement of seeds in the soil, and this resulted in the lowest number of seeds per hole. It is consistent with Ormond et al (2018) that the seed-metering device operating at lower speeds had better performance in the seeding process.…”
Section: Resultssupporting
confidence: 88%
“…It was observed that the seed metering mechanism on the seed drill implements performed better in regulating the placement of seeds in the soil, and this resulted in the lowest number of seeds per hole. It is consistent with Ormond et al (2018) that the seed-metering device operating at lower speeds had better performance in the seeding process.…”
Section: Resultssupporting
confidence: 88%
“…Tal fato foi demonstrado por Ormond et al (2018), operando nas velocidades de 2,0; 4,7; 6,5; 9,1 e 10,3 km h -1 , com os melhores percentuais de espaçamentos aceitáveis nas velocidades até 6,5 km h -1 , indicando que o aumento da velocidade pode acarretar aumento dos espaçamentos falhos e múltiplos para a cultura do milho, comprometendo a eficácia da semeadura. Carpes et al (2017) verificaram que, com o aumento da velocidade periférica do disco dosador de sementes, há uma tendência de redução no nível de precisão de deposição das sementes na linha de semeadura, diminuindo os espaçamentos aceitáveis entre plântulas.…”
Section: Introductionunclassified
“…Although the structure of the mechanical seed-metering device is simple, it is designed strictly in accordance with the seeds' shape and volume, limiting its versatility [10] . Another shortcoming of the device is that seeds are prone to be damaged in seeding processes due to physical contacts [11,12] .…”
Section: Introduction mentioning
confidence: 99%